Rancang Bangun Purwarupa Alat Bantu Pengukuran dan Pemotongan Gulungan Material Di Retail Bahan Bangunan - Agustina Christiani (Jurnal Rekayasa Sistem Industri, 2022)
This research was conducted by taking a case study of a retail store that sells various kinds of building materials. Workers in this shop found it difficult to measure and cut any roll-shaped materials. In addition to a longer time to measure and cut the materials, workers also experienced several kinds of pain after doing these activities. Based on the result of Cornell Musculoskeletal Discomfort Questionnaire (CMDQ), it was known that the workers experienced pain in their lower back (23.6%), upper back (20.5%), waist (14.1%) and neck (12.7%). Therefore, in this research, a tool will be designed to make it easier for workers to measure and cut roll-shaped material. The design was carried out based on the results of body posture analysis using the REBA (Rapid Entire Body Assessment) method. The improvement of the worker's posture was carried out by making a tool for measuring and cutting roll-shaped materials. The 3D model for the tool was developed by using the CATIA application. The design of the tool is in the form of a support with 2 rollers which have a total dimension of 150 cm long, 50 cm wide and 110 cm high.  Based on REBA analysis, it was known that there was a significant decrease in REBA scores from 11 (high risk level) for the current work posture to 3 (low risk level) in the proposed work posture using the designed tool. This decreasing of the REBA score happened because the tool was designed so that workers can operate it in a standing position with a roller at elbow height. To ensure that the designed tool could work properly, a prototype of the tool was made in a small scale model. In addition to accomodating ergonomic posture, the tool prototype also could measure the material automatically. The measurement automation process uses Arduino as the main microcontroller which will regulate the motion of the stepper motor used.